The Return of Unregistered Movable Cultural Property of the Colonial Philippines: Perspectives in International Law - Tantuico, Kathleen Felise Constance D. (Diliman, Quezon City, Philippines: University of the Philippines College of Law)
The Philippines, an archipelago in Southeast Asia, is known for enduring over three hundred years of colonial rule from three different masters--Spain, the United States and Japan--from 15th to 20th Centuries. Over the course of colonial rule, a significant number of historical objects and cultural materials have been removed from the Philippines and are currently on display in various museums around the world. Now, after decades of being considered an independent State, numerous historical and cultural materials still remain in the possession of foreign entities. The extent and number of cultural objects, to this day remains undocumented, and remedies under local and international laws for their return have yet to be explored. This note examines the domestic and international laws that may provide fir perspectives that can facilitate the repatriation of cultural property obtained from the Philippines during colonial rule.
Keywords: Cultural property - Philippines - International law; Cultural property - Philippines